2006
DOI: 10.1089/jam.2006.19.456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dry Powder Inhaler Resistance on the Inspiratory Flow Rates and Volumes of Cystic Fibrosis Patients of Six Years and Older

Abstract: Several inhaled drugs for use by cystic fibrosis (CF) patients are formulated for nebulizer use only. This therapy is time consuming and includes the risk of contamination of the nebulizers. Dry powder inhalers (DPI) can be an attractive alternative for CF drugs. Inhaled flow rate and volume, and the device resistance are important determinants for optimal dispersion of drug from a DPI. It is important to understand how these variables interact in the CF population in order to properly design a new DPI formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 24 publications
6
50
0
4
Order By: Relevance
“…This may be counterintuitive since the youngest, sickest children should have the most difficulty generating the required flow and volume necessary to ensure the aerosol reaches the lower airways. Tiddens et al 23 investigated this concept in a study in which inspiratory profiles of CF subjects of varying ages and disease severities were recorded using several resistors to simulate the representative resistance of a dry powder inhaler. By reproducing the inspiratory profiles representative of the T-326 inhaler in vitro with a breath simulator, researchers demonstrated that even a low inspired flow of 30 L/min and volume of 0.6 L could empty 14 and to the low-to-medium resistance of the T-326 inhaler.…”
Section: Discussionmentioning
confidence: 99%
“…This may be counterintuitive since the youngest, sickest children should have the most difficulty generating the required flow and volume necessary to ensure the aerosol reaches the lower airways. Tiddens et al 23 investigated this concept in a study in which inspiratory profiles of CF subjects of varying ages and disease severities were recorded using several resistors to simulate the representative resistance of a dry powder inhaler. By reproducing the inspiratory profiles representative of the T-326 inhaler in vitro with a breath simulator, researchers demonstrated that even a low inspired flow of 30 L/min and volume of 0.6 L could empty 14 and to the low-to-medium resistance of the T-326 inhaler.…”
Section: Discussionmentioning
confidence: 99%
“…One advantage of utilizing a patient's inspiratory airflow as the main source of energy is that such devices are breath actuated; this inherently avoids the need to synchronize the actuation and inspiration maneuver by the patient. The downside of this approach is that devices currently available show a device-specific airflow resistance, and this often demands a relatively high inspiratory effort (31) which might be a hurdle for patient populations suffering from obstructive airway diseases such as asthma or COPD, the elderly, or very young (32). The extent of lung deposition is also dependent on the individual patient's inspiratory flow rate causing a potential difference in the dose effectively delivered due to this variability (33).…”
Section: General Requirements For Dry Powder Inhalation Devicesmentioning
confidence: 99%
“…TIP has an MMAD ,4 mm and a grain size distribution of 1.7-2.7 mm [50]. The low-resistance inhaler allows the patient to generate a wide range of inspiratory flows [51]. In a controlled laboratory setting, it was shown that almost all CF patients of 6 years and older were able to generate flows of o30 L?min -1 .…”
Section: Dpis: the Basicsmentioning
confidence: 99%
“…Unfortunately, as discussed, high inspiratory flows increase oropharyngeal deposition and can reduce lung deposition, especially in the small airways. To empty all drug from the TIP capsule, an inspiratory volume of 1 L is sufficient to release all dry powder [51]. Most patients of 6 years and older were able to inhale a volume of o1 L [51].…”
Section: Dpis: the Basicsmentioning
confidence: 99%
See 1 more Smart Citation